ANALYSIS OF THE ASSESSMENT OF ADMISSION CONTRIBUTIONS AGAINST LOCAL REVENUES - Siska Yulia Defitri Defitri; Delsi Afrini; Yandi Putra; Nidia Anggreni Das; Rasidah Nasrah (Jurnal Ekonomi, 2022)
The effectiveness of regional revenue sources becomes a reference for the regions in preparing regional budgets and expenditures for the next period. The source of revenue that shows regional performance in increasing revenue comes from the area itself in increasing local revenue (PAD), namely taxes and fees because community participation is very dominant and is a factor for regional success in developing its area if the community participates a lot, contributing income to the area in the form of taxes and levies. Quantitative descriptive research is the aim of this study, to determine the amount of local tax contributions in generating regional income. The data uses time series data for 5 (five) years from 2017-2021. T he average PAD growth for Solok City in a period of 5 five years from 2017 -2021, has a growth of 0.38 percent per year, while the effectiveness of achieving PAD is already high, namely an annual average of 93.9. Compared to the contribution between taxes and levies that have a higher contribution to PAD is local taxes. This result can be interpreted that the participation of the people of Solok City in paying regional taxes is greater.